Peptides from Euphausia superba Promote Longitudinal Bone Growth by Accelerating Growth Plate Chondrocyte Proliferation and Hypertrophy - Dai, Yufeng; Li, Zhuo; Fu, Meng; Li, Yanqi; Xue, Changhu; Wang, Jingfeng (Current Pharmaceutical Biotechnology, 2021)
Background: With the improvements in living standards, height is getting more attention. Malnutrition is one of the main causes of children's short stature; therefore, nutritional intervention in adolescence is the key to prevent short stature. The peptides from Antarctic Krill (AKPs), the ideal protein model, act in bone formation and anti-osteoporosis. However, the studies on promoting longitudinal bone growth by AKPs have not been reported. Methods: Three-week-old male ICR mice, to construct the adolescent mice model, randomly divided into three groups: normal group, casein group (casein, 300 mg/kg·BW), and AKPs group (AKPs, 300 mg/kg·BW). After 21 days of drug administration, the effects of AKPs on serum biochemical indexes and femur histomorphology of mice, and the mechanism of AKPs promoting longitudinal bone growth was discussed. Results: AKPs significantly increased longitudinal bone growth and improved bone strength. In addition, AKPs remarkably promoted proliferation and hypertrophy of chondrocytes in the growth plate. The further mechanism revealed that AKPs increased serum Growth Hormone (GH) and Insulin-Like Growth Factors-1(IGF-1) contents, which activated the downstream GH/IGF-1 axis signaling pathways. Moreover, AKPs induced the secretion and expression of bone morphogenetic protein 2 (BMP- 2) and triggered the activation of BMP2-dependent Smads signaling. AKPs also activated Wnt/ β-catenin signaling, and synergistically activated the expression of Runt-related transcription factor 2 (Runx 2) and Osterix (OSX). Conclusion: AKPs promoted longitudinal bone growth by activating GH/IGF-1 axis, BMP-2/Smads and Wnt/β-catenin pathways, suggesting AKPs to be a potential nutrient fortifier for longitudinal bone growth.
Keywords: Peptides from antarctic krill